Comprehensive profiling of novel epithelial–mesenchymal transition mediators and their clinical significance in colorectal cancer - Satoshi Ishikawa (Nature Portfolio, 2021)
Abstract Epithelial–mesenchymal transition (EMT) is a drastic phenotypic change during cancer metastasis and is one of the most important hallmarks of aggressive cancer. Although the overexpression of some specific transcription factors explains the functional alteration of EMT-induced cells, a complete picture of this biological process is yet to be elucidated. To comprehensively profile EMT-related genes in colorectal cancer, we quantified the EMT induction ability of each gene according to its similarity to the cancer stromal gene signature and termed it “mesenchymal score.” This bioinformatic approach successfully identified 90 candidate EMT mediators, which are strongly predictive of survival in clinical samples. Among these candidates, we discovered that the neuronal gene ARC, possibly originating from the retrotransposon, unexpectedly plays a crucial role in EMT induction. Profiling of novel EMT mediators we demonstrated here may help understand the complexity of the EMT program and open up new avenues for therapeutic intervention in colorectal cancer.